The Stacked Community Engagement model: A practical model for developing community-engaged academic medical faculty. Issue 1 (11th January 2023) - Johnston, Bryan; Ruffalo, Leslie; Nelson, David; O'Connor, Sarah; Petterson, Erika; Young, Staci
Abstract: Introduction: There is an increasing recognition of the benefits of sustained community engagement (CE) that accrue to academic health centers and the communities they serve. However, the success and sustainability of CE projects rely on the efforts of individual faculty, learners, and community members, for whom CE efforts are typically added to their professional and personal priorities and responsibilities. This competition for time and resources between priorities and CE can discourage academic medical faculty from participating in CE activities. The Stacked Community Engagement model is proposed to synergize or "stack" responsibilities and goals onto the scaffolding of CE projects. Methods: We examined the literature and expert CE practitioner opinion to identify the challenges faced by community-engaged academic faculty and the key characteristics of CE projects that successfully align and integrate with the priorities of faculty, learners, and community members. We synthesized this information to develop the conceptual Stacked CE model for developing CE academic medical faculty, then illustrated the model in heterogeneous CE programs to explore its generalizability, validity, and robustness. Results: The Stacked CE model, when applied to a specific nutrition education program (The Food Doctors) and outreach program (StreetLife Communities), provided a practical framework for examining the sustained success of a partnership between Medical College of Wisconsin faculty and medical students and the community. Conclusions: The Stacked CE model is a meaningful framework for developing community-engaged academic medical faculty. By identifying overlap and integrating CE into professional activities with intention, CE practitioners can benefit from the deeper connections and sustainability.